2022
DOI: 10.3389/fphar.2022.841657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adolescent Intermittent Ethanol Exposure on Social Investigation, Social Preference, and Neuronal Activation in cFos-LacZ Male and Female Rats

Abstract: Adolescence is a sensitive developmental period during which alcohol use is often initiated and consumed in high quantities, often at binge or even high-intensity drinking levels. Our lab has repeatedly found that adolescent intermittent ethanol (AIE) exposure in rats results in long-lasting social impairments, specifically in males, however our knowledge of the neuronal underpinnings to this sex-specific effect of AIE is limited. The present study was designed to test whether social anxiety-like alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…It has previously been shown that AIE exposure reduces activity-regulated cytoskeletal (Arc) gene expression Pandey 2015), decreases brain derived neurotrophic factor (BDNF) (Pandey 2015), and lowers neuropeptide Y protein (Kokare 2017) in the CeA, with these alterations associated with various behavioral impairments such as anxietylike behavior (Kokare et al, 2017;Kyzar et al, 2019;Kyzar et al, 2017;Pandey et al, 2015). In our previous study, reduced neuronal activation of the CeA was evident in AIE-exposed males, whereas females displayed a moderate increase in CeA neuronal activation (Towner et al, 2022a). These contradicting findings clearly show that more work is needed to understand the long-term consequences of AIE on CeA neuronal activation between sexes.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It has previously been shown that AIE exposure reduces activity-regulated cytoskeletal (Arc) gene expression Pandey 2015), decreases brain derived neurotrophic factor (BDNF) (Pandey 2015), and lowers neuropeptide Y protein (Kokare 2017) in the CeA, with these alterations associated with various behavioral impairments such as anxietylike behavior (Kokare et al, 2017;Kyzar et al, 2019;Kyzar et al, 2017;Pandey et al, 2015). In our previous study, reduced neuronal activation of the CeA was evident in AIE-exposed males, whereas females displayed a moderate increase in CeA neuronal activation (Towner et al, 2022a). These contradicting findings clearly show that more work is needed to understand the long-term consequences of AIE on CeA neuronal activation between sexes.…”
Section: Discussionmentioning
confidence: 88%
“…Prior work from our lab has found that AIE consistently results in sex-specific social deficits evident in adulthood (Dannenhoffer et al, 2018; Towner et al, 2022a; Varlinskaya et al, 2020; Varlinskaya et al, 2017; Varlinskaya et al, 2014). Specifically, males exposed to ethanol during adolescence show decreased social preference and social investigation, with these findings absent in females.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations